The philosophy of true wealth - Abdul Razak, Mohd Abbas (Center for Community Development and Education (CCDE) Banda Aceh, 2025)
I don’t know the value of millions of dollars in the bank. I don’t know the worth of an expensive car or a private jet. I don’t know the luxury of a palace or a villa. But I know the worth of a good book, A beautiful poem, good music, And a meaningful philosophy of life. I can feel the pain of someone who is sick, The weight of a serious illness dragging them down. From ancient times, we’ve been told That gold, diamonds, rubies, emeralds, And all other precious stones are priceless— But I simply like to look at them, And I’m not concerned with how much they’re worth At the gem market. I’ve never dreamed of possessing them. When friends try to impress me with expensive items, I politely turn them down,